Penile strangulation by a metal ring - Alva, Ajay G; Warat, Ravi; Balsarkar, Dharmesh J; Balsarkar, Mihir D; Suryawanshi, Sachin A (Indian Journal of Case Reports, 2024)
Penile strangulation due to the metallic ring is an uncommon clinical entity that requires urgent attention to prevent irreversible nerve damage, and if neglected gangrene of the penis. Various methods have been described in the literature for removing constricting foreign bodies, but there is no consensus regarding an acceptable technique. We report the case of a 51-year-old man with a history of a metal ring used for sexual pleasure lodged over the shaft of his penis with an inability to remove the same.